Global community breaks at 60 m on mesophotic coral reefs. Issue 10 (24th June 2019) - Lesser, Michael P.; Slattery, Marc; Laverick, Jack H.; Macartney, Keir J.; Bridge, Tom C.
Abstract: Aim: Mesophotic coral ecosystems (MCEs) are unique communities that support a high proportion of depth‐endemic species distinct from shallow‐water coral reefs. However, there is currently little consensus on the boundaries between shallow and mesophotic coral reefs and between upper versus lower MCEs because studies of these communities are often site specific. Here, we examine the ecological evidence for community breaks, defined here as species loss, in fish and benthic taxa between shallow reefs and MCEs globally. Location: Global MCEs. Time period: 1973–2017. Major taxa studied: Macrophytes, Porifera, Scleractinia, Hydrozoa, Octocorallia, Antipatharia and teleost fishes. Methods: We used random‐effects models and breakpoint analyses on presence/absence data to identify regions of higher than expected species loss along a depth gradient of 1–69 m, based on a meta‐analysis of 26 studies spanning diverse photoautotrophic and heterotrophic taxa. We then investigated the extent to which points of high faunal turnover can be explained by environmental factors, including light, temperature and nutrient availability. Results: We found evidence for a community break, indicated by a significant loss of shallow‐water taxa, at ~ 60 m across several taxonomically and functionally diverse benthic groups and geographical regions. The breakpoint in benthic composition is best explained by decreasing light, which is correlated with the optical depths between 10 and 1% of surface irradiance. A concurrent shift in the availability of nutrients, both dissolved and particulate organic matter, and a shift from photoautotroph to heterotroph‐dominated assemblages also occurs at ~ 60 m depth. Main conclusions: We found evidence for global community breaks across multiple benthic taxa at ~ 60 m depth, indicative of distinct community transitions between shallow and mesophotic coral ecosystems. Changes in the underwater light environment and the availability of trophic resources along the depth gradient are the most parsimonious explanations for the observed patterns.